Benzamide capped peptidomimetics as non-ATP competitive inhibitors of CDK2 using the REPLACE strategy. Issue 15 (1st August 2016) - Premnath, Padmavathy Nandha; Craig, Sandra N.; Liu, Shu; McInnes, Campbell
Graphical abstract: Abstract: Inhibition of cyclin dependent kinase 2 (CDK2) in complex with cyclin A in G1/S phase of the cell cycle has been shown to promote selective apoptosis of cancer cells through the E2F1 pathway. An alternative approach to catalytic inhibition is to target the substrate recruitment site also known as the cyclin binding groove (CBG) to generate selective non-ATP competitive inhibitors. The REPLACE strategy has been applied to identify fragment alternatives and substituted benzoic acid derivatives were evaluated as a promising scaffold to present appropriate functionality to mimic key peptide determinants. Fragment Ligated Inhibitory Peptides (FLIPs) are described which potently inhibit both CDK2/cyclin A and CDK4/cyclin D1 and have preliminary anti-tumor activity. A structural rationale for binding was obtained through molecular modeling further demonstrating their potential for further development as next generation non ATP competitive CDK inhibitors.